2017
DOI: 10.1111/ejn.13754
|View full text |Cite
|
Sign up to set email alerts
|

System‐specific activity in response to Δ9‐tetrahydrocannabinol: a functional magnetic resonance imaging study in awake male rats

Abstract: The aim of this study was to assess the effects of two doses of Δ -tetrahydrocannabinol (THC, cannabis' main psychoactive agent) and vehicle on blood-oxygen-level dependent (BOLD) activity in drug-naïve, awake rats, in an effort to obtain a THC-specific map of activation in clinically-relevant regions and systems. Intraperitoneal injections of low dose of THC resulted in increased positive and negative BOLD signals compared to vehicle and high dose in areas rich in cannabinoid receptor 1, as well as throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
2
2
Order By: Relevance
“…Both VBM and DWI in this study on adult female mice revealed changes in the accumbens, ventral pallidum and caudate putamen, key brain areas high in afferent connections from the midbrain DA system. The sensitivity of these areas to Δ9-THC is consistent with the preclinical literature ( Kolb et al, 2006 ; Madularu et al, 2017 ). Interestingly, the Coleman study on periadolescent mice exposed to vaporized cannabis found no change in the DA system with VBM and a modest change in ADC values, and only then to the accumbens core ( Coleman et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…Both VBM and DWI in this study on adult female mice revealed changes in the accumbens, ventral pallidum and caudate putamen, key brain areas high in afferent connections from the midbrain DA system. The sensitivity of these areas to Δ9-THC is consistent with the preclinical literature ( Kolb et al, 2006 ; Madularu et al, 2017 ). Interestingly, the Coleman study on periadolescent mice exposed to vaporized cannabis found no change in the DA system with VBM and a modest change in ADC values, and only then to the accumbens core ( Coleman et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…The absence of BOLD signal change in brain areas between the rostral/caudal axis of the brain (e.g., hippocampus, sensorimotor cortices, thalamus, hypothalamus, amygdala, and basal ganglia) made this pattern of activation and deactivation especially intriguing. This is unlike anything reported in awake animal imaging following tests on numerous CNS active drugs (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Here we show the positive and negative changes in BOLD signal occur within 10 min of injection, and while CBD is known to rapidly penetrate the brain within seconds following systemic administration (46), its effects could be orchestrated easily by both peripheral and central targets.…”
Section: Polarized Positive and Negative Boldcontrasting
confidence: 81%
“…The absence of BOLD signal change in brain areas between the rostral/caudal axis of the brain (e.g., hippocampus, sensorimotor cortices, thalamus, hypothalamus, amygdala, and basal ganglia) made this pattern of activation and deactivation especially intriguing. This is unlike anything reported in awake animal imaging following tests on numerous CNS active drugs [8][9][10][11][39][40][41][42][43][44][45][46][47]. Here we show the positive and negative changes in BOLD signal occur within 10 min of injection, and while CBD is known to rapidly penetrate the brain within seconds following systemic administration [48], its effects could be orchestrated easily by both peripheral and central targets.…”
Section: Polarized Positive and Negative Boldcontrasting
confidence: 81%